Mutually Engaging Encounter with the Use of Technology (MEET) between grandparents and grandchild an explanatory framework on closeness as a family outcome - Gonzalez, Armel B.
Technology and stress are part of our daily lives. With the challenges we face every day, people can easily get isolated and unstable. This study aims to provide an explanatory framework on closeness as a family outcome from the mutually engaging encounter with the use of technology (MEET) between a grandparent and a grandchild.